Parasitic-compensated quadrature LC oscillator - Boon, Chirn Chye (2011)
The paper presents a method for improving the phase noise performance of a CMOS quadrature LC oscillator through parasitic compensation. Owing to the parasitic resistance in the inductor, the LC oscillator suffers from a low Q-value, which degrades its phase noise performance. In this design, through the parasitic-compensation method, the LC oscillator will be made to oscillate at the frequencywhen the effective impedance of the parallel LC resonator is at the peak.